Locating a zeitgeist: Displacement, becoming and the end of alterity. (September 2019) - Hinkson, Melinda
As displacement and dislocation become increasingly widespread human experiences, the future-focused analytic of becoming is gaining considerable traction in anthropological theorising. This article explores what an emphasis on becoming precludes from view. As anthropologists chase fine-grained understandings of human life on the move, while also attempting to account for the discipline's colonial legacy, it is increasingly common to find place-based alterity dismissed as no longer relevant, or to find it reduced to little more than abstract products of colonial imaginaries, forms of domination and totalising social theory. Ethnography of Warlpiri displacement describes vigorous practices through which people creatively draw forth, refashion and deploy place-based certainties of the past to tackle the pressing challenges of the present. Exploring this ethnography against diverse settings of displacement, I argue that a fully engaged contemporary anthropology would attend to the ways in which people under duress continue to draw upon distinctively place-based concepts, principles and associations to endure and reimagine the circumstances of their lives.